English foreign language teaching anxiety of Indonesian pre-service teachers of undergraduate internship program - Huyi Intan Sari; Choiril Anwar (Universitas Islam Sultan Agung, 2021)
Anxiety is a topic mostly investigated in the field of foreign language education. Unfortunately, the main focus of the studies on the aforementioned topic has primarily been provided in relation to anxiety suffered by students not teachers. Anxiety in speaking English while teaching has been proven to be a separate obstacle to the success of the language teaching and learning. This still happens to teachers who even have years of teaching experience. This study aims to investigate the English language teaching anxiety as experienced by the pre-service teacher at the department. The FLTA questionnaire consisting of 27 out of 45 items was adopted to collect data. Since this study was carried out during the COVID-19 pandemic, the questionnaire was distributed to the participants via email. The analysis was then made by implementing the qualitative descriptive approach and simple quantification to support the description. The results show that there were five factors of anxiety occur during the program. They were teaching inexperience, self-perception of language proficiency, fear of negative evaluation, lack of student’s interest, and difficulty with time management. These findings are expected to become a reference for the efforts of developing an internship preparation program.